Public Sector Reform and Citizenship Welfare in Post-Colonial Nigeria: A Case Study of Oil Subsidy Regime - Isonah , Teddy Ionagbe; Okutalukwe, Chidiebere T. (Kashere Journal of Politics and International Relations, 2025)
The trajectory of public sector reform in Nigeria from state led to market economy directed by the law of demand and supply has increased the justification for profit maximization in service delivery. This has created serious consequences to the welfare of her citizens in provision of essential services. The public sector reform was organized to delegitimize the state involvement in the management of production and exchange of goods and service. The philosophy behind this reform connotes the global triumph of capitalism over socialism and the attendant invocation of market principles to determine the provision of service delivery. Nigeria, being a post-colonial integrated economy into the global capitalism has adopted the logic of neoliberalism in pricing of her petroleum product by the elimination of subsidy from fuel by President Bola Ahmed Tinubu’s government. The removal of the petroleum subsidy (fuel) bears severe impact on the affordability, security of supply and accessibility of the product on the citizens’ welfare. The studies intend to utilize qualitative research approach in its data gathering and analysis. This study articulates that maintaining the principles of public sector in the distribution and pricing of petroleum products contribute to major ingredients of social stability and equilibrium in the provision of development and security in Nigeria. The logic of maintaining subsidy in petroleum product cannot be conceived as a burden but a stabilizer and stimulator of the welfare of people.